2020
DOI: 10.1155/2020/8861557
|View full text |Cite
|
Sign up to set email alerts
|

Similar Repair Effects of Human Placenta, Bone Marrow Mesenchymal Stem Cells, and Their Exosomes for Damaged SVOG Ovarian Granulosa Cells

Abstract: Background. This study is aimed at investigating the repairing effect of mesenchymal stem cells and their exosomes from different sources on ovarian granulosa cells damaged by chemotherapy drugs—phosphoramide mustard (PM). Methods. In this study, we choose bone marrow mesenchymal stem cells (BMSCs) and human placental mesenchymal stem cells (HPMSCs) for research. Then, they were cocultured with human ovarian granulosa cells (SVOG) injured by phosphoramide mustard (PM), respectively. β-Galactosidase staining, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Follicular reserve and ovarian function are measures of reproductive endocrine functionality and fertility potential (14). OGCs play important roles in the regulation of follicle activation, growth, development, and atresia (15). Recently, several studies targeting speci c genes and regulating various signaling pathways have shown that lncRNAs have vital roles in the formation and development of ovarian follicles (16-18).…”
Section: Discussionmentioning
confidence: 99%
“…Follicular reserve and ovarian function are measures of reproductive endocrine functionality and fertility potential (14). OGCs play important roles in the regulation of follicle activation, growth, development, and atresia (15). Recently, several studies targeting speci c genes and regulating various signaling pathways have shown that lncRNAs have vital roles in the formation and development of ovarian follicles (16-18).…”
Section: Discussionmentioning
confidence: 99%
“…All data were expressed as the mean ± standard deviation (SD). Sample size was set based on the results of other previous studies [ 43 45 ]. Comparisons were performed with the Student t -test or one-way ANOVA for experiments with more than two subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…All data were expressed as the mean ± standard deviation (SD). Sample size was set based on the results of other previous studies [43][44][45].…”
Section: Macroscopic and Histological Evaluation Of Articularmentioning
confidence: 99%
“…Due to the unique life cycles of N. gonorrhoeae and C. trachomatis, the major PID caused by these infections are chronic, so antibiotic therapy is less effective, which often leads to persistence of the infection and reinfection (Chen et al, 2020). Various studies listed in Table 1 have reported the positive effects of MSC-Exos in the treatment of gynecological diseases (Sun et al, 2019;Zhang et al, 2019;Xin et al, 2020;Zhao et al, 2020;Lee et al, 2021;Liao et al, 2021).…”
Section: Therapeutic Potential Of Mesenchymal Stem Cell-derived Exosomes On Salpingitis Induced By N Gonorrhoeae and C Trachomatis Infectmentioning
confidence: 99%